Retroperitoneal Paraganglioma Mimicking Pancreas Cancer: A Case Report - Özsoy, Mustafa; Haskaraca, Mehmet Fatih; Alpaydın, Turgay (Fırat University, 2012)
The outside settlement of adrenal gland in pheochromocytoma is called paraganglioma. Retroperitoneal area which is outside settlement of adrenal gland is considerable for paraganglioma. In this area paragangliomas are more malignant and more functional than the others. Clinical picture depends on whether the mass of hormone is active or not. Although most of patients are asymptomatic, they are recognized through the medium of radiology. 47 year old female, was admitted with jaundice, abdominal pain. CA19-9 was found to be elevated in blood test and the patient's abdominal CT scan revealed mass which was arised from pancreas. The patient was operated with the diagnosis of pancreatic cancer while intraoperative observation of pancreas was found to be normal. Retroperitoneal mass, which did not allow manual manipulation due to hypertensive cause attacks and was sitting on the vena cava, was found. The mass was removed en bloc vena cava clamping. In histopathological examination, retroperitoneal paraganglioma was found out. According to anatomical location, paraganglioma are confused with primary retroperitoneal cancers, especially pancreas malignancy. Herein, we present primary retroperitoneal paraganglioma which is mimicking pancreas neoplasm.

Feokromasitomanın, adrenal bezi dışında yerleşimine paraganglioma adı verilir. Adrenal bez dışında retroperitonel bölge paraganglioma için özellikli bir bölgedir. Bu lokalizasyonda paragangliomalar daha malign ve daha fonksiyoneldir. Klinik, kitlenin hormon aktif olup olmamasına bağlı değişiklik göstermektedir. Fakat hastaların büyük çoğunluğu asemptomatiktirler ve görüntüleme yöntemlerinde insidental olarak saptanan kitle ile tanı alırlar. 47 yaşında bayan, sırta vuran karın ağrısı ve sarılık şikayeti nedeniyle başvurdu. Laboratuar incelemelerinde CA 19-9 yüksekliği saptanan hastanın karın tomografisinde pankreas başından kaynaklanan kitle gözlendi. Pankreas kanseri ön tanısıyla operasyona alınan hastanın intraoperatif gözleminde pankreasın normal olduğu gözlendi. Retroperitoneal bölgeden kaynaklanan vena kava üzerine oturmuş ve elle manipülasyona izin vermeyen hipertansif ataklara neden olan retroperitonal kitle saptandı. Kitle vena kava klempajı ile enblok çıkartıldı. Histopatolojik incelemede ise retroperitoneal paraganglioma tanısı konuldu. Lokalizasyonları nedeniyle paragangliomalar başta pankreas kanseri olmak üzere diğer retroperitonel tümörler ile karışabilmektedir. Bu makalede pankreas kanserini taklit eden retroperitonel paraganglioma olgusunu sunmaktayız.
Pankreas Kanserini Taklit Eden Retroperitonel Paraganglioma Olgusu